The impact of sleep problems on cerebral aneurysm risk is mediated by hypertension: a mediated Mendelian randomization study - Yan, Xiaofei; Li, Hongwu (Frontiers in Genetics, 2024)
Introduction Cerebral aneurysm (CA) is a common vascular disease. The risk factors of CA include hypertension, smoking, and a family history of genetic predisposition. Although sleep-related problems have been found to have a strong association with cardiovascular disease, there is a lack of research regarding the causal relationship with cerebral aneurysms. Methods In this study, we investigated the causal relationship between four sleep-related problems, including snoring, insomnia, narcolepsy, and napping during the day, and CA using a two-sample Mendelian randomization (MR) analysis. Moreover, the potential confounders before sleep problems and CA were further analyzed by multivariate MR (MVMR). Results The causal relationship between insomnia and CA was obtained analytically by means of six MR analyses. There was a strong causal effect relationship between insomnia and CA, which suggests this as a potential risk factor [odds ratio (OR) = 8.35, 95% confidence interval (CI) = 2.422–28.791, p = 7.772e-04]. On this basis, hypertension was identified as a mediator between insomnia and CA by MVMR, with a mediating effect of 52.538% (OR = 3.05, 95% CI = 1.549–4.55, p = 0.015). Conclusion The causal relationship between insomnia and CA was predicted using genetic variance data, and insomnia was found to be a potential risk factor. Furthermore, hypertension is a mediator between insomnia and CA. Therefore, focusing on sleep problems and improving sleep quality may be an active and effective strategy to prevent CA.